Assessment of Selected Heavy Metals Levels in Soil from the Athi-Thwake River Catchment Area, Makueni County, Kenya - Kariuki Sarah M; Abong’o Deborah A; Kithure Joyce G.N; Obiero John P.O (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This study assessed the levels of lead, zinc, copper, chromium, cadmium, nickel, iron, and manganese in soil samples from ten specific sites within the Athi-Thwake River catchment area in November 2021 and January 2022, representing the wet and dry seasons respectively in Makueni County. The samples were analyzed using an Atomic Absorption Spectrophotometer (AAS) and data by IBM SPSS 20. The metal levels ranged from 0.10 ± 0.03 mg/kg - 188.02 ± 3.69 mg/kg. In the dry season, the order of metal levels was iron > lead > zinc > manganese > copper > chromium > cadmium > nickel these values were compared with the World Health Organization (WHO) recommended limits for soil quality. Zinc and copper levels were within the WHO limits of 5.0 mg/kg and 10 mg/kg, respectively. However, the mean levels of lead, cadmium, nickel, iron, and manganese in both the wet and dry seasons showed significant differences (p<.05) and exceeded WHO limits of 0.1 mg/kg, 0.1 mg/kg, 0.003 mg/kg, 0.05 mg/kg, 55 mg/kg, and 0.5 mg/kg, respectively, while copper and chromium showed no statistical significance (p>.05). The study revealed the importance of conducting thorough soil analysis, specifically focusing on heavy metals in the ten selected sites. The study showed the presence of high levels of these metals in soil in the catchment area and this could be impacting negatively on the ecosystem health of the area.